A Protective HLA Extended Haplotype Outweighs the Major COVID-19 Risk Factor Inherited From Neanderthals in the Sardinian Population - Mocci, Stefano; Littera, Roberto; Tranquilli, Stefania; Provenzano, Aldesia; Mascia, Alessia; Cannas, Federica; Lai, Sara; Giuressi, Erika; Chessa, Luchino; Angioni, Goffredo; Campagna, Marcello; Firinu, Davide; et al. (Frontiers in Immunology, 2022)
Sardinia has one of the lowest incidences of hospitalization and related mortality in Europe, and yet a very high frequency of the Neanderthal risk locus variant on chromosome 3 (rs35044562), considered to be a major risk factor for a severe SARS-CoV-2 disease course. The protection conferred by the HLA-A*02, B*18, DRB*03 three-loci extended haplotype in the Sardinian population seems to efficiently contrast the high risk of a severe and devastating outcome of the infection predicted for carriers of the Neanderthal locus. This result suggests that the balance between risk and protective immunogenetic factors plays an important role in the evolution of COVID-19. A better understanding of these mechanisms may well turn out to be the biggest advantage in the race for the development of more efficient drugs and vaccines.